Strategy for the Development of Trail Running as a Sports Tourism Activity in the Area of Batur Mountain, Bangli, Bali - I Wayan Suyasa Ariantha; I Nyoman Sunartha; Ketut Antara (CV. AFDIFAL MAJU BERKAH, 2023)
The development of sports tourism in Bangli Regency is now being carried out more vigorously, notably in the Mount Batur area, which has numerous potentials. The growth of sports tourism is now being prioritized. Perhaps tourists only know Bali as a water sports paradise, but Bali also has numerous appealing sports tourism sites and has become a staple on the world-class sports tourism agenda. Seeing this potential, the purpose of this study is to examine and propose a development strategy for trail running as a sports tourist activity in the Mount Batur area, beginning with recognizing the potential and elements that influence its development. This research uses qualitative and quantitative approaches. The research informants consisted of related tourism stakeholders and 100 tourists as respondents. The results showed that there are internal and external factors, each of which is analyzed in the IFAS/EFAS matrix. The score on the IFAS matrix is 2.54 and the EFAS matrix is 2.73. From the SWOT matrix analysis, 11 alternative strategies were obtained. Furthermore, the QSPM matrix was used to examine the various strategies to establish the priority strategies that can be utilized in the development of trail running as a sports tourist activity in the Mount Batur area of Bangli, Bali. The analysis results suggest that the approach of allocating admission tickets to tourist attractions in the Mount Batur area is favored because it has the highest overall attractiveness score (TAS) of 8.37 points.